(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
This article describes a system of poetic forms and stylistic features of the cycle of sonnets «Amoretti» by English poet-humanist XVI century Edmund Spenser. Graphics, spelling, phonetic, lexical, syntactic methods, which determine the specificity of the poetic cycle were characterized.